Transesterifikasi In Situ Biji Jarak Pagar Menggunakan Kavitasi Hidrodinamik - Muhammad Dani Supardan; Satriana Satriana; Ryan Moulana (agriTECH, 2014)
In this study, the in situ transesterification of jatropha seed using hydrodynamic cavitation for the production of biodieselwas studied. Experiments were carried out under the following conditions: 800 mL of methanol volume, 50oC of reaction temperature, 2 g of potassium hidroxide catalyst, less than 3% of moisture content in jatropha seed and 0,355-1,18 mm of particle size. From experiment without co-solvent addition, the highest biodiesel yield of 35% obtained at condition: time of process of 120 minute and ratio of methanol to jatropha seed of 16 (mL/g) . The use of co-solvent of hexane provided a higher yield of biodiesel compared to the system without co-solvents. The highest biodiesel yield of 60% were obtained under the addition of 95 mL of hexane volume. In addition, the use hydrodynamic cavitation provided a higher yield of biodiesel compared to the system using mechanical stirring. The biodiesel produced in the experiment was analyzed by gas chromatography-mass spectrometry (GC-MS), which showed that methyl oleate was the highest compound in biodiesel.ABSTRAKPenelitian ini bertujuan untuk mempelajari proses produksi biodiesel dari biji jarak pagar melalui proses transesterifikasi in situ menggunakan kavitasi hidrodinamik. Transesterifikasi in situ dilakukan pada kondisi: volume metanol 800 mL, temperatur proses 50oC, katalis kalium hidroksida 2 g, kandungan air biji jarak kurang dari 3% dan ukuran partikel biji jarak 0,355-1,18 mm. Hasil penelitian menunjukkan rendemen biodiesel tertinggi sebesar 35% yang dihasilkan dari proses transesterifikasi in situ biji jarak pagar menggunakan kavitasi hidrodinamik tanpa penambahan co-solvent diperoleh pada penggunaan waktu proses 120 menit dan rasio volume metanol terhadap berat biji jarak 16 (mL/g). Penggunaan co-solvent heksana terbukti dapat meningkatkan rendemen biodiesel yang dihasilkan dimana pada penambahan volume heksana sebanyak 95 mL diperoleh rendemen biodiesel sebesar 60%. Proses transesterifikasi in situ biji jarak menggunakan kavitasi hidrodinamik menghasilkan rendemen biodiesel yang lebih besar dibandingkan proses menggunakan pengaduk mekanik. Hasil analisis gas chromatography-mass spectrometry (GC-MS) menunjukkan komponen terbesar dalam produk biodiesel adalah metil oleat.